2022
DOI: 10.3389/fpubh.2022.981270
|View full text |Cite
|
Sign up to set email alerts
|

Health impacts with telework on workers: A scoping review before the COVID-19 pandemic

Abstract: BackgroundTelework has dramatically increased due to the coronavirus disease 2019 (COVID-19) pandemic, and the health impacts related to telework have become major concerns. Some studies have shown that telework has both positive and negative impacts. However, during the pandemic, the influence of COVID-19 is too strong to estimate the health effects of telework. Therefore, this scoping review investigated a comprehensive overview of those impacts based on studies conducted before the COVID-19 pandemic.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Working from home might, on the one hand, be associated with negative side effects such as higher levels of musculoskeletal pain ( 54 ), depression or alcohol consumption ( 55 , 56 ), less physical activity, etc ( 57 ). On the other hand, working from home might lead to a reduction of contacts with infected individuals, longer sleeping times, more time for physical activity, an enhanced possibility to arrange working and personal life and better productivity ( 58 , 59 ). Further research with a health equity focus is needed to fully understand the effect of working from home on individuals’ health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Working from home might, on the one hand, be associated with negative side effects such as higher levels of musculoskeletal pain ( 54 ), depression or alcohol consumption ( 55 , 56 ), less physical activity, etc ( 57 ). On the other hand, working from home might lead to a reduction of contacts with infected individuals, longer sleeping times, more time for physical activity, an enhanced possibility to arrange working and personal life and better productivity ( 58 , 59 ). Further research with a health equity focus is needed to fully understand the effect of working from home on individuals’ health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown an increase in mental health issues owing to the COVID-19 pandemic ( 13 , 48 50 ). General distress and reduced social contacts, including remote work, had detrimental effects on mental health, increasing stress, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, these results indicate that teleworking predates the recent pandemic crisis. However, it might say that this new modality of work is an emerging and current phenomenon, which, by necessity, gained new momentum with COVID-19 [ 78 ] and which already allows us to guide an appropriate response to the first research question. From March 2020 onwards, the world was affected by a phenomenon that required adaptation to the numerous restrictions imposed, and the work sphere was no exception [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that teleworking can influence workers’ behavior, regardless of the services or positions held (e.g., teaching, administrative, psychologists, and hospital staff). That is, irrespective of the role performed, workers are exposed to a set of factors that can trigger different pathologies, a finding found mainly among female workers [ 9 , 19 , 22 , 55 , 68 , 69 , 71 , 78 , 79 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation